The Resilience of Surgical Mask Supply Chain during Epidemic– A Case Study in Taiwan - Chang, Jia-Ning (2020)
Recently, the world is in turbulent times which is never seen before, that forces millions of people work from home, millions of students learn from online lectures, thousands manufactures suspend, more than half airlines stop flight, because of the novel coronavirus outbreak globally. Therefore, many countries try to induce the infection spreading under lockdown policy and block national boundary to keep citizens safety and economy. Due to the globalization and containerization, China has exported more than half of world surgical mask, but China has restricted their amount of export to reach the domestic high demand after the COVID-19 took plan in Wuhan. Consequently, international procurement of personal protection equipment such as surgical masks has become fierce competition between nations as heavily rely on global outsourcing for low-value products. To solve the disruption of supply chain for surgical mask, Taiwan government ban the export of surgical mask on 23 January 2020, and announce the policy of central control surgical mask while reorganizing the supply chain network in Taiwan, as well as declare ration-plan of purchasing surgical mask. The targets of all policies are to increase the resilience of supply chain and protect people safety. Thus, Taiwan has been one of the countries nearby China without lockdown policy and become the second most production for surgical mask worldwide. This study will analysis the factors of successful raising production and reorganizing the supply chain of surgical mask based on the culture feature, national health system, and industrial capacity, as well as evaluate the national disaster protection and prevention plan by MOHW. Hence, this research uses Taiwan as case study of resilience supply chain during virus epidemic to provide useful method of improving current prevention plans for future disasters including infectious virus.